Assessment of quality of vegetable products according to electric characteristics - Мідик, Ігор-Михайло Володимирович (Technology audit and production reserves, 2016)
Vegetables are important food products, therefore practical methods of control for concentrations of useful and harmful elements in vegetables make actual issue for the research. Vegetable juice is object of the research. Subject of the audit is defined by dependence of electrical properties of juice, containing sodium and cuprum ions on concentrations of these substances in the juice. Aim of the research is to develop a quick method to determine concentration of useful minerals and harmful substances in the vegetable juice according electrical parameters. The method of control for quality parameters of vegetable juice, proposed by the author, is based on immittance method. Main units of measuring tools for immittance control of quality parameters of vegetable juice are a capacitive transducer, RLC-meter and block of results processing and control (PC). Principle of measuring tools operation expects: under laboratory conditions the model fluids are created, i.e. carrot juices of known characteristics, which are placed in a capacitive transducer with square graphite electrodes which are completely immersed in the liquid; RLC-meter in asynchronous mode transfers a test signal to the capacitive transducer; in response the model liquid characteristics come to the RLC-meter (active and reactive components of the electric conductivity of juice). Studies of the model fluids have resulted in determination of dependency of active and reactive component of the conductivity on chemical nature and concentration of useful minerals and harmful substances. The measured values are compared to the set values for comparison. Results of the comparison help to make conclusions about content of harmful substances. Measuring is done in few seconds and can be used in real production conditions for quick quality control of vegetables.